Meta-Analysis: Effect of Social Media on Anxiety Disorders in Adolescents - Rizki Aqsyari D; Hendra Dwi Kurniawan; Retno Dewi Prisusanti; Julhan Irfandi (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2024)
As technology develops, technology also has an impact on every aspect of life, including the psychology of every human being. The imbalance created by excessive social media use is of great concern to parents, researchers, and society regarding the mental health of individuals experiencing anxiety. Social media is ubiquitous among teens, who are also at high risk for anxiety disorders. This research aims to conclude that social media has an effect on anxiety disorders. This research uses a systematic review and meta-analysis using PICO. Population: teenagers. Intervention: social media. Comparison: not social media. Outcome: anxiety. The articles used in this research come from 1 database, namely Google Scholar. The keywords of the article are “teenager” AND “social media” AND “anxiety” AND “multivariate”. The articles included in this research are full paper articles, cross-sectional study design, publication year range 2017-2024 and the magnitude of the Adjusted Odds Ratio relationship. Articles were analyzed using the Review Manager 5.4 application. Five cross-sectional studies showed that social media can increase the risk of anxiety disorders by 1 times greater than not using social media, and the results were statistically (aOR=1.00; 95% CI= 0.63 to 1.57; p= 0.01). Teenagers who use social media increase anxiety disorders.